2018
DOI: 10.3389/fimmu.2018.02061
|View full text |Cite
|
Sign up to set email alerts
|

The Dual Nature of Type I and Type II Interferons

Abstract: Type I and type II interferons (IFN) are central to both combating virus infection and modulating the antiviral immune response. Indeed, an absence of either the receptor for type I IFNs or IFN-y have resulted in increased susceptibility to virus infection, including increased virus replication and reduced survival. However, an emerging area of research has shown that there is a dual nature to these cytokines. Recent evidence has demonstrated that both type I and type II IFNs have immunoregulatory functions du… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
502
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 536 publications
(514 citation statements)
references
References 99 publications
(124 reference statements)
9
502
0
3
Order By: Relevance
“…However, each cytokine play its own role in the immune response, whether it stimulates the inflammatory process or not. Our results showed that KM1608 enhanced the mRNA expressions of IFN-α, -β, and IL-10, consistent with the previous studies that type-I IFNs stimulate the IL-10 expression in macrophages [38].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…However, each cytokine play its own role in the immune response, whether it stimulates the inflammatory process or not. Our results showed that KM1608 enhanced the mRNA expressions of IFN-α, -β, and IL-10, consistent with the previous studies that type-I IFNs stimulate the IL-10 expression in macrophages [38].…”
Section: Discussionsupporting
confidence: 93%
“…They also promote the IL-10 expression in macrophages. Type-I IFNs not only trigger the antiviral immune response, but also downregulate this response to limit the tissue damage [38]. In addition, type-I IFNs participate in the antitumor activity by promoting the adaptive immune response of CD8+ T-cells which controls tumor growth.…”
Section: Discussionmentioning
confidence: 99%
“…The roles of other cytokines in EV‐A71 pathogenesis are little understood. Involvements of these cytokines in disease pathogenesis have also been observed in other viral infections . IL‐β is secreted by activated macrophages.…”
Section: Host Immune Responses To Ev‐a71 Infectionmentioning
confidence: 86%
“…However, the discovery of the IFNLR on neutrophils and DCs suggests a more broad function for this cytokine during respiratory pathogen to protect the barrier response (54). Type II IFN is largely secreted by natural killer (NK) cells (55) and recruited CD8 + T cells (56) in response to IAV infection, and IFNγ signals the local macrophage populations that express the receptor IFNGR to promote phagocytosis, reactive bursts, and the production of proinflammatory cytokines (57).…”
Section: Epithelial-resident Leukocyte Crosstalk During Early Iav Infmentioning
confidence: 99%